Indonesian Trias Politica Analysis: A Study of Constitutional Court Decision Number 90/PUU-XII/2023 concerning the Age Limit for Presidential and Vice Presidential Candidates - Fernando, Fikri Gali; Ardiyansyah, Yuda Nur; Kurnia, Tria Nindy; Wulandari, Tiara Wahyu Meyda; Wangsa, Maulana Adi (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2024)
This study aims to analyze the Constitutional Court Decision Number 90/PUU-XII/2023 using an analytical tool, namely the concept in Trias Politica. This research uses a normative type (doctrinal) with a (Case approach). The data in this study used primary and secondary data, including national legislation and other relevant literature. Implementation of the Indonesian Trias Politica concept is different from the pure Montesquiue trias politica. This is because of the examinative power occupied by (BPK). The DPR is referred to as a positive legislator. Therefore, the Constitutional Court is referred to as a negative legislator. Thus, the Constitutional Court Decision No. 90/PUU-XII/2023 which adds a phrase to Judicial Review in Article 169 letter q of Law No. 7 of 2017 concerning Elections, normatively contradicts the authority of the DPR as a positive legislator listed in Article 20 paragraph (1) of the 1945 Constitution. Based on Trias Politica's analysis, Constitutional Court Decision No. 90/PUU-XII/2023 concerning Decisions 29/PUU-XXI/2023, 51/PUU-XXI/2023, and 55/PUU-XXI/2023, the Court thinks that regarding the age in article 169 letter (q) of Law No. 7 of 2017, it is the authority to form laws and to amend them. This is certainly contrary to the principle of open legal policy where this principle is oriented toward the DPR as a positive legislature or as a framer of laws and to change it. This is certainly contrary to the principle of open legal policy where this principle is oriented towards the DPR as a positive legislature or as a framer of laws contained in Article 20 paragraph (1) of the 1945 Constitution and Article 173 letter (b) of the MD3 Law which states that the authority and duties of the DPR are carried out by discussing, drafting, and disseminating bills.